DEVELOPING ENGLISH INTERACTIVE MULTIMEDIA STUDENTSâ EâWORKSHEET FOR FOURTH GRADERS OF ELEMENTARY SCHOOL - Arifin, Haris Rizqi (Language Circle: Journal of Language and Literature, 2014)
Technology can change the paradigm of teacher-centered to be student-centered. One of the advantages of the technology is in making multimedia material. Multimedia material is one type of media that can be used as the solution to improve the student motivations in doing tasks in the worksheet. This study is a Research and Development of designing an E-Worksheet which is based on multimedia technology and internet network. There are seven stages to develop this E-Worksheet. They are Need Analysis, Product Design, Expert and Teacher Validation, First Product Revision, Field Test, Second Product Revision and Final Product. This study aims at developing interactive multimedia eâworksheet for the fourth graders of elementary school. It was tried out to the students and the results the studentsâ interest, motivation, and concentration in learning English, by using the Interactive Multimedia E-Worksheet was high. The level of difficulty of the E-Worksheet was well. The studentsâ activeness was very high. From these findings, it is suggested that English teachers need to learn how to design and develop multimedia material by using various computer programs. For Students, they should be control in utilizing computer and internet.